COMPARISON OF DIFFERENT TREATMENT MODALITIES OF CHELATION THERAPY IN BETA THALASSEMIA MAJOR PATIENTS - Usman, Ghazal; Mahfooz ur Rehman; Khalil, Shifa; Hafeez, Muhammad Sarmad (Journal of Ayub Medical College Abbottabad, 2024)
Background: Thalassemia has high prevalence and carrier rate of 8 - 10% in Pakistan, repeated blood transfusions lead to iron deposition in organs. In this Prospective study we have compared the efficacy of three chelation regimens being used in our country. It has been conducted at PBTS, Fatmid Foundation and Children Hospital Lahore. Methods: 60 thalassemia major patients, were divided into 3 groups according to their mode of chelation. Patients in group I were on oral iron chelator deferiprone, 7 days per week. Thalassemics in group II were on parenteral iron chelator deferoxamine given subcutaneously for 4 days in a week, and group III patients were on combination therapy, deferiprone for 5 days & deferoxamine given twice weekly. The assessment of chelation was done by measurement of serum ferritin and 24 hour urinary iron excretion at the start of study and then after six months of follow up. To assess the hepatic iron, hepatic MRI were also performed. Results: Ferritin levels were maximally decreased in group II, followed by group III, with no significant reduction in group I. However statistically significant difference in mean urinary iron excretion (increased) was seen in group III. The hepatic iron was very high in all three groups as shown by the hepatic MRI. Conclusion: Combination chelation therapy is the most effective chelation therapy in iron overloaded patients. It helps improve the compliance and increases urinary iron excretion. Patients on DFX have lowest degree of hepatic siderosis even though it is considerably higher than normal population.